2009
DOI: 10.1149/1.3152325
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-Free Pt Electrocatalysts Supported on SnO[sub 2] for Polymer Electrolyte Fuel Cells

Abstract: Carbon-free Pt-based electrocatalysts supported on semiconducting SnO 2 ͑Pt/SnO 2 ͒ have been developed for polymer electrolyte fuel cells ͑PEFCs͒ by various electrochemical and microstructural characterizations. Pt/SnO 2 exhibited comparable currentvoltage characteristics to conventional Pt electrocatalysts and, in particular, a considerable tolerance against 10,000 cycles of voltages up to 0.9 and 1.3 V RHE ͑RHE denotes reversible hydrogen electrode͒ vs the RHE. These results indicate that the carbon-free ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
126
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(133 citation statements)
references
References 25 publications
2
126
0
1
Order By: Relevance
“…After the high potential oxidation, the Pt/SnO 2 reserved as much as 89.7% of its initial ECA and the CV of SnO 2 seldom changed, indicating that the use of SnO 2 as a catalyst support significantly improved the catalyst resistance against high potential. According to the literature [16,17], SnO 2 is the most stable compound in the Sn-H 2 O system at 80 • C which is similar to typical PEMFC operation conditions.…”
Section: Electrochemical Propertiesmentioning
confidence: 67%
See 2 more Smart Citations
“…After the high potential oxidation, the Pt/SnO 2 reserved as much as 89.7% of its initial ECA and the CV of SnO 2 seldom changed, indicating that the use of SnO 2 as a catalyst support significantly improved the catalyst resistance against high potential. According to the literature [16,17], SnO 2 is the most stable compound in the Sn-H 2 O system at 80 • C which is similar to typical PEMFC operation conditions.…”
Section: Electrochemical Propertiesmentioning
confidence: 67%
“…Tin oxide (SnO 2 ), with n-type semiconducting property and good electrochemical stability, has been proposed as a potential catalyst support material for fuel cell application [10][11][12][13][14][15][16][17][18]. Previous studies have shown that SnO 2 can promote the electro-oxidation of CO, methanol, and ethanol due to the formation of OH species at low potentials and the strengthened metal-support interaction [19,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, electronic conductive oxides or nitrides have been examined as stable supports for PEFCs, e.g., Pt/SnO2 [18,19], Pt/TiO2 [20][21][22][23], Pt/Ti4O7 [24,25], Pt/TiN [26], among others. The support materials used are typically in the form of nanoparticles with HSA to disperse Pt catalyst particles uniformly, but the use of HSA supports often leads to a high contact resistance between the particles.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 To address these problems, many efforts have been devoted to investigate new electrode materials and design new nanostructures of electrode material. [6][7][8][9] Particularly, metal oxide/graphene composites are emerging as a kind of promising materials for lithium-ion batteries because these materials have superior electrical conductivities than graphite. Among them, tin oxide (SnO 2 ) has attracted much attention because of its high lithium storage capacity up to 782 mAhg −1 , more than twice as that of graphite.…”
mentioning
confidence: 99%